2020
DOI: 10.12688/gatesopenres.13122.1
|View full text |Cite
|
Sign up to set email alerts
|

Reduced dengue incidence following deployments of Wolbachia-infected Aedes aegypti in Yogyakarta, Indonesia: a quasi-experimental trial using controlled interrupted time series analysis

Abstract: Background: Ae. aegypti mosquitoes stably transfected with the intracellular bacterium Wolbachia pipientis (wMel strain) have been deployed for biocontrol of dengue and related arboviral diseases in multiple countries. Field releases in northern Australia have previously demonstrated near elimination of local dengue transmission from Wolbachia-treated communities, and pilot studies in Indonesia have demonstrated the feasibility and acceptability of the method. We conducted a quasi-experimental trial to evaluat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
153
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(160 citation statements)
references
References 30 publications
5
153
1
1
Order By: Relevance
“…In contrast, the utilization of strains associated with low-to-mild fitness costs, albeit with generally lower PI, allow fewer individuals to be released in the field in order to promote an efficient invasion. Fulfilling these criteria, the strain w Mel has been advocated as a standard choice for field release, collecting successful trials in Australia, Brazil and Indonesia (Garcia et al, 2019; Hoffmann et al, 2014, 2011; Indriani et al, 2020; O’Neill et al, 2019; Ryan et al, 2019; Tantowijoyo et al, 2020). Nonetheless, due to its beneficial attributes in warmer climates, keeping density levels high and stable, w AlbB has proven a second option and suitable alternative to w Mel, as shown by a recent trial held in Malaysia (Nazni et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the utilization of strains associated with low-to-mild fitness costs, albeit with generally lower PI, allow fewer individuals to be released in the field in order to promote an efficient invasion. Fulfilling these criteria, the strain w Mel has been advocated as a standard choice for field release, collecting successful trials in Australia, Brazil and Indonesia (Garcia et al, 2019; Hoffmann et al, 2014, 2011; Indriani et al, 2020; O’Neill et al, 2019; Ryan et al, 2019; Tantowijoyo et al, 2020). Nonetheless, due to its beneficial attributes in warmer climates, keeping density levels high and stable, w AlbB has proven a second option and suitable alternative to w Mel, as shown by a recent trial held in Malaysia (Nazni et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent field trials demonstrated that deployment of the w Mel strain into local Ae. aegypti populations can result in a reduction of local dengue transmission [ 16 , 17 ]. Despite the effectiveness of Wolbachia ’s viral protection, the mechanism(s) that underlies the ability of Wolbachia to control the virus replication is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti . Recently, several strains of the endosymbiont Wolbachia pipientis (Alphaproteobacteria: Ricketsiales ) have been used in integrated arboviral control programs around the world [ 14 , 15 , 16 , 17 ]. On account of the fact that Ae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When Wolbachia infected mosquitoes were released into the wild, the bacterium spread through the mosquito populations by cytoplasmic incompatibility (Hoffmann et al, 2011;Walker et al, 2011). Large field trials have shown that this approach can decrease dengue prevalence in human populations (Indriani et al, 2020;Ryan et al, 2020). A great advantage of this method to control arboviruses is that Wolbachia can block the replication of not only dengue virus, but also chikungunya, yellow fever, Zika and West Nile viruses (Moreira et al, 2009;Glaser and Meola, 2010;van den Hurk et al, 2012;Aliota et al, 2016).…”
Section: Wolbachia Virus Blockingmentioning
confidence: 99%